Pattern of Recurrence in Locally Advanced Carcinoma Cervix Based on Platinum Sensitivity (Medical Forum Monthly, 2023)
Objective: To validate the concept of platinum sensitivity in cervical cancer women and estimate its effect.Study Design: Prospective studyPlace and Duration of Study: This study was conducted at the Nishtar hospital Multan from May 2022 to April 2023.Materials and Methods: A total of 60 patients diagnosed as IB2 and IVA proven histologically as squamous cell carcinoma or adenocarcinoma were enrolled. Platinum-based chemotherapy is a standard treatment for patients with advanced cervical cancer (ACC). Platinum drugs, such as cisplatin and carboplatin, are commonly used in combination with other chemotherapy agents to treat ACC.Results: The mean age of the patients was 54.63±3.55 years. All the sixty patients were given chemotherapy with cisplatin-based regimens. Most of the patients 51.7% had <6 months of relapse, whereas, locoregional was the most common pattern of relapse, 73.3%. Most of the patients had loco-regional and <6 months of relapse time and 9 patients had distant relapse pattern and >18 months of relapse time, (p<0.001).Conclusion: Platinum sensitivity concept can be applied to advanced cervical cancer patients, with evidence showing a significant role on survival of women after recurrence in women who were treated with platinum chemotherapy previously.